PRINCIPAL EIGENVALUES FOR THE FRACTIONAL p-LAPLACIAN WITH UNBOUNDED SIGN-CHANGING WEIGHTS - ASSO, Oumarou; DOUMATE, TELE JONAS; CUESTA, Mabel; LEADI, Liamidi (My University, 2023)
After establishing the boundedness and regularity of weak solutions, we prove that this problem admits principal eigenvalues under certain conditions. We also show that when such eigenvalues exist, they are simple and isolated in the spectrum of the operator.
Keywords: Fractional p-Laplacian; fractional Sobolev space; indenite weight; principal eigenvalues.